Step up approach for the management of late presentation of pancreatic trauma patients - Ahmad, Shabi; Singh, Vikram; Pandey, Vinod Kumar; Kumar, Shirish; Alam, Tabrej; Pratap, Prakhar (International Surgery Journal, 2020)
Background: Pancreatic injuries are usually subtle to identify by different diagnostic imaging modalities and these injuries are often overlooked in cases with extensive multi-organ trauma. Our study was conducted to evaluate the outcome of a step-up approach in the management of pancreatic trauma patients with late presentation. Methods: The study included 15 patients who presented with grade III AAST delayed presentation of pancreatic trauma from September 2017 to 2019. In our step-up approach 2 staged procedure was done, firstly laparotomy with necrosectomy along with closure of proximal pancreatic duct with external drainage of pancreatic duct, in second stage Roux-en-Y pancreaticojejunostomy was done to drain the remnant pancreas as a definitive procedure 3 to 6 months after initial procedure. Results: In our study, blunt trauma abdomen (83.30%) (n=10) was the most common mode of injury. The main reason for delay in diagnosis of pancreatic trauma was delayed presentation of patient (83.3%) (n=10). Total of 4 patients were admitted to intensive care unit (ICU) at the time of admission. 10 patients underwent both the stages of step up approach management among which one patient had pancreatic fistula as a complication (n=1) (10%) and one patient had post-operative abscess as a complication (n=1) (10%). No mortality was noted in our study. Conclusions: The step-up approach discussed above proves to be beneficial towards management of patients with delayed presentation of pancreatic trauma in our setting.